Epigenetics and chromatin plasticity in embryonic stem cells - Přikrylová, Terézia; Pacherník, Jiří; Kozubek, Stanislav; Bártová, Eva (World journal of stem cells, 2013)
The study of embryonic stem cells is in the spotlight in many laboratories that study the structure and function of chromatin and epigenetic processes. The key properties of embryonic stem cells are their capacity for self-renewal and their pluripotency. Pluripotent stem cells are able to differentiate into the cells of all three germ layers, and because of this property they represent a promising therapeutic tool in the treatment of diseases such as Parkinson's disease and diabetes, or in the healing of lesions after heart attack. As the basic nuclear unit, chromatin is responsible for the regulation of the functional status of cells, including pluripotency and differentiation. Therefore, in this review we discuss the functional changes in chromatin during differentiation and the correlation between epigenetics events and the differentiation potential of embryonic stem cells. In particular we focus on post-translational histone modification, DNA methylation and the heterochromatin protein HP1 and its unique function in mouse and human embryonic stem cells.
Keywords: Chromatin; Epigenetics; Nucleus; Differentiation; Pluripotency; Embryonic stem cells